Chemical composition of some wild peanut species (Arachis L.) seeds - Grosso, Nelson (2000)
Oil, protein, ash and carbohydrates contents, iodine value, fatty acid composition and sterol composition were studied in seeds of Arachis trinitensis, A. chiquitana, A. kempff-mercadoi, A. diogoi, , A. benensis, A. appresipila, A. valida, A. kretschmeri, A. kuhlmannii, A. williamsii, A. sylvestri, A. matiensis, A. pintoi, A. hoehnei, A. villosa and A. stenosperma. Oil content was greatest in A. stenosperma (mean value = 51.8%). The protein level was higher in A. sylvestris (30.1%) and A. villosa (29.5%). Mean value of oleic acid varied between 30.6% (A. matiensis) and 46.8% (A. villosa), and linoleic acid oscillated between 34.1% (A. villosa) and 47.4% (A. appresipila). The better oleic-to-linoleic (O/L) ratio was exhibited by A. villosa (1.38). Some species showed higher concentration of behenic acid. The greatest level of this fatty acid was found in A. matiensis (6.2%). Iodine value was lower in A. valida (99.2). The sterol composition in the different peanut species showed higher concentration of sitosterol (mean value oscillated between 55.7 and 60.2%) followed by campesterol (12.4-16.5%), stigmasterol (9.7-13.3%), and avenasterol (9.7-13.4%). The chemical quality and stability of oils (iodine value and O/L ratio) from wild peanut studied in this work are not better than those of cultivated peanuts.